2012
DOI: 10.1530/erc-11-0387
|View full text |Cite
|
Sign up to set email alerts
|

Novel candidate genes of thyroid tumourigenesis identified in Trk-T1 transgenic mice

Abstract: For an identification of novel candidate genes in thyroid tumourigenesis, we have investigated gene copy number changes in a Trk-T1 transgenic mouse model of thyroid neoplasia. For this aim, 30 thyroid tumours from Trk-T1 transgenics were investigated by comparative genomic hybridisation. Recurrent gene copy number alterations were identified and genes located in the altered chromosomal regions were analysed by Gene Ontology term enrichment analysis in order to reveal gene functions potentially associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…TRK‐T1 is a fusion protein composed of the carboxyl terminal tyrosine kinase domain of NTRK1 and the amino terminal portion of TPR, TRK‐T1 fusion protein is enough to cause the occurrence of PTC . In TRK‐T1 fusion protein transferred thyroid mouse tumour model, TRK‐T1 could alter gene expression and promote cancer progression . In our results, high MTDH expression was found in PTC.…”
Section: Discussionsupporting
confidence: 52%
“…TRK‐T1 is a fusion protein composed of the carboxyl terminal tyrosine kinase domain of NTRK1 and the amino terminal portion of TPR, TRK‐T1 fusion protein is enough to cause the occurrence of PTC . In TRK‐T1 fusion protein transferred thyroid mouse tumour model, TRK‐T1 could alter gene expression and promote cancer progression . In our results, high MTDH expression was found in PTC.…”
Section: Discussionsupporting
confidence: 52%
“…Besides, PDLIM5 was considered necessary in cell migration by forming lamellipodia, and phosphorylation inactivation of PDLIM5 was reported to weaken the cell metastasis capacity by inactivating RAC1 [ 10 ]. According to recent studies, PDLIM5 may participate in the progression of many types of cancer including thyroid cancer [ 11 ], lung cancer [ 12 ], breast cancer [ 13 ] and gastric cancer [ 14 ]. Koutros et al [ 15 ] reported that PDLIM5 mRNA was overexpressed in PCa tissues by using gene chip detection.…”
Section: Introductionmentioning
confidence: 99%
“…As an actin adaptor protein, PDLIM5 is not only involved in cytoskeletal tissue, cellular processes, and organ development, but is also considered to play roles in tumorigenesis and development (Eeckhoute, 2006;Edlund et al, 2012;Heiliger et al, 2012;Li et al, 2015). PDLIM5 is expressed in many cancer cell lines.…”
Section: The Role Of Pdlim5 In Tumormentioning
confidence: 99%
“…Dysfunction of the proteins of the PDZ-LIM family is known to affect the maintenance of organ function and weaken the invasion ability and metastatic potential of cancer cells (Bagheri-Yarmand et al, 2006;Tanaka-Okamoto et al, 2009). According to recent studies, PDLIM5 may be involved in the progression of multiple tumor types (Eeckhoute, 2006;Edlund et al, 2012;Heiliger et al, 2012;Li et al, 2015). The important role of PDLIM5 in various organizational systems have led to a deeper understanding of its physiological function.…”
Section: Introductionmentioning
confidence: 99%